1970
DOI: 10.3329/imcj.v2i1.2928
|View full text |Cite
|
Sign up to set email alerts
|

A Follow Up on Biochemical Parameters in Dengue Patients Attending BIRDEM Hospital

Abstract: During a one-year period between January to December 2002, a total of 84 cases were clinically diagnosed as dengue in the medical unit I of BIRDEM. They were classified into 4 groups: dengue fever (28), DHF-I (31), DHF-II (17), and DHF-III (8). Amongst the patients, 52 (61.9%) were males and 32 (38.1%) were females. SGPT and SGOT were above normal cutoff (40 IU) points in 64 (76.2%) and 73(86.9%) cases respectively. SGOT was higher than SGPT in most cases. S. Bilirubin was almost normal in all cases. S. Calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…12 Therefore, AST, ALT are valuable parameters for the evaluation of the severity of the disease. In a study carried out by Nguyen et al 13 and Uddin KN et al, 14 AST values were reported to be frequently abnormal, reaching values higher than those of ALT, we have found similar findings in our study. 15 Therefore, AST, ALT are valuable parameters for the evaluation of the severity of the infection.…”
Section: Discussionsupporting
confidence: 92%
“…12 Therefore, AST, ALT are valuable parameters for the evaluation of the severity of the disease. In a study carried out by Nguyen et al 13 and Uddin KN et al, 14 AST values were reported to be frequently abnormal, reaching values higher than those of ALT, we have found similar findings in our study. 15 Therefore, AST, ALT are valuable parameters for the evaluation of the severity of the infection.…”
Section: Discussionsupporting
confidence: 92%
“…Calcium entry via neuronal calcium channels is essential for neurotransmission, hence calcium plays an important role in the smooth functioning of the autonomic nervous system [12]. Uddin et al reported that the mean total calcium levels were significantly lower in patients with DHF than in patients with uncomplicated dengue fever (DF) [13]. However, free calcium is a more useful index than total calcium and provides a better indication of calcium status [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hypocalcemia has been documented in dengue infection[ 3 4 5 ] and is seen more frequently in patients with severe dengue. [ 4 ] Nonetheless, evidence with regards to the role of calcium homeostasis in dengue is limited, and current recommendations do not mention the need to monitor or correct blood calcium levels in dengue.…”
Section: Introductionmentioning
confidence: 99%